2011
DOI: 10.1186/1752-1947-5-297
|View full text |Cite
|
Sign up to set email alerts
|

'Boiled egg' in the peritoneal cavity-a giant peritoneal loose body in a 64-year-old man: a case report

Abstract: IntroductionPeritoneal loose bodies, or peritoneal mice, are rare asymptomatic lesions that are usually found as an incidental finding during abdominal surgery or autopsy. Giant loose bodies, measuring more than 5 cm, are rare and only a few cases are reported in the literature. These bodies are usually infarcted appendices epiploicae, which become detached and appear as a peritoneal loose body in the abdominal cavity. They may re-attach themselves to a surface, such as the lower aspect of the spleen or omentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 8 publications
0
30
0
1
Order By: Relevance
“…Although the majority of PLBs range from 0.5 to 2.5 cm in diameter and generally cause no symptoms,7 they can reach a diameter of 5 to 9.5 cm and are then termed "giant" PLBs. Because of the limited room in the pelvic bowl, giant PLBs can compress pelvic structures, resulting in intestinal obstruction, incomplete bowel emptying, and urinary retention 3-5,9. The most common radiological finding of a PLB is an oval-shaped mass with a central calcification and a low-intensity area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of PLBs range from 0.5 to 2.5 cm in diameter and generally cause no symptoms,7 they can reach a diameter of 5 to 9.5 cm and are then termed "giant" PLBs. Because of the limited room in the pelvic bowl, giant PLBs can compress pelvic structures, resulting in intestinal obstruction, incomplete bowel emptying, and urinary retention 3-5,9. The most common radiological finding of a PLB is an oval-shaped mass with a central calcification and a low-intensity area.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few cases of giant PLBs have been reported in the literature 2-5,8,9,11-13. Even though these patients were asymptomatic, surgery was performed to remove the suspected neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the giant peritoneal loose body was 50 × 40 × 40 mm in size and did not cause any discomfort; it was found incidentally on physical examination. Occasionally, if the peritoneal loose bodies are large enough and in a particular location, patients may be admitted to the hospital with acute urinary retention [ 4 , 5 ] or intestinal obstruction [ 6 - 8 ] due to extrinsic compression.…”
Section: Case Presentationmentioning
confidence: 99%
“…Matsubara et al (3) reviewed 20 reported PLB cases and determined that PLB is more common in males, with a male:female ratio of 17:3. Although the pathogenesis of PLB remains unclear, it is widely accepted that they arise from infarcted appendices epiploicae, which then go through several sequential processes, including saponification, calcification and fibrosis (4). PLBs then increase in size by accumulating albumin from exudative peritoneal fluid (4).…”
Section: Introductionmentioning
confidence: 99%